Security Vision of 5G - Hongru Zhu; Xiaojun Zhuang; Shu Guo; Minpeng Qi (Dianxin kexue, 2014)
With the commercial use of 4G, the research of 5G is being carried out in full swing in the industry. 5G will have a revolutionary change in the bandwidth, speed, intelligence and integration. So on the security front, 5G inevitably will have corresponding change. The security architecture, the security key technologies and the future research direction of the security mechanism of 5G were discussed.